Makna Simbolik Musik Daak Maraaq dan Daak Hudoq dalam Upacara Hudoq Bahau di Samarinda Kalimantan Timur - Asril Gunawan (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2020)
The Symbolical Meaning Daak Maraaq Music and Daak Hudoq of Hudoq Bahau Ritual in Samarinda, East Borneo. The ritual of Hudoq is an annual cultural practice performed by Dayak Bahau people in the city of Samarinda. The performance of this ritual consists of some phases in which every phase of it represents the symbolical meaning closely related to the value of the ritual. Those phases are (1) Lemivaa Lalii’; (2) Hudoq Taharii’; (3) Lemivaa Tasam; (4) Hudoq Kawit; and (5) Hudoq Pakoq.  Daak Maraaq and Daak Hudoq music and Hudoq dance are performed during the ritual. Daak Maraaq and Daak Hudoq are two different kinds of music, both have a different style of performance, stage of performance, and style of music. Due to its complexity, it becomes especially important to analyze the role of the symbolical meaning of music performed in the ritual of Hudoq. This is a qualitative research within an ethnomusicological approach—music within the cultural perspective—which is done through an analytical descriptive method. The theoretical approach used for this case study is symbolic interpretation and music (transcription) analyses. Despite analyzing the symbolical meaning of Daak Maraaq and Daak Hudoq music, this research is done to provide important information about musical analyses—within the ethnomusicological perspective—of that music. According to the data collected, the ritual of Hudoq has an important role in performing the symbolical meaning of the identical value of ritual, social, and existential meaning for the lives of Dayak Bahau people in Samarinda city, East Borneo.